Substitusi Tepung Kulit Manggis (Garcinia Mangostana) Pada Pembuatan Cake Diukur Kadar ß-Karoten Dan Daya Terima - UTAMA, Arif Sandi Surya, Eni Purwani, S.Si., M.Si, Pramudya Kurnia, STP, M.Agr (2015)
Background : The number of mangosteene production can generate the problem of environment especially which is because of waste from mangosteen husk after its contents consumed, to overcome the problem generated by mangosteene husk (G. Mangostana) one of them is exploit the mangosteen husk become the flour of mangosteen husk. Obstetrical of nutrient flour of mangosteen husk cover the provitamine A 8,03%, protein 3,02 gram, fat 6,45% and carbohydrate 82,55%. Tujuan : This research aim to know the influence of subtitution flour of mangosteen husk to rate ß- karoten and energy accepted. Method: Research type is experiment. Research device used by a random device complete with three treatment of cake of mangosteen husk 0%, 10%, 20% and 30% Result: Result of test show content ß- karoten cake of mangosteen husk that is repetition I that is 2.484 (mg/ 100g), 2.505 (mg/100g), 2.493 (mg/100g) and 2.653 (mg/100g), while repetation II that is 2.512 (mg/ 100g), 2.469 ( mg / 100g), 2.413 (mg / 100g) and 2.580 ( mg / 100g). Energy accepted to be got by that hobby storey to colour and feel the most cake taken a fancy to by panelist of there are at ca ke treatment 10%, teksture, most aroma entirety and in taking a fancy to by panelist of there are at cake treatment 30%. There are influence significant to colour cake (p=0,000), feel the cake (p=0,006), tekstur cake (p=0,000) and entirety cake (p=0,012). Especially for the aroma of there no influence significant to aroma cake (p=0,095) and do not give the influence significant to rate ß- karoten cake ( p=0,000) Conclusion : There are influence influence addition of cake substitution flour of mangosteen hus k to colour cake (p=0,000), feel the cake (p=0,006), tekstur cake (p=0,000) and entirety cake ( p=0,012). But do not there are influence at giving influence significant to measure ß- karoten cake ( p=0,325)